Faktor- Faktor yang Mempengaruhi Lama Rawat Inap Pada Pasien Ckb di Rumah Sakit Mardi Rahayu Kudus Tahun 2021 - Maria Novita Sari; Galia Wardha Alvita (Indonesian Journal of Nursing Research (IJNR), 2022)
Severe head injury or traumatic brain injury is currently one of the most common causes of disability and death globally since the head is the most crucial part of humans. There are several factors that can affect severe head injury patients with acute subdural haemorrhage, i.e. the time between trauma and evaluation of bleeding. Based on observations made at the Mardi Rahayu Kudus Hospital test.This growth depended on the triggering factors in the realm of health services. This study aims to determine the factors related to the length of hospitalization of TBI patients at Mardi Rahayu Kudus Hospital. The type of this research is Retrospective with a cross-sectional study design. The population in this study were all patients diagnosed with TBI at Mardi Rahayu Kudus Hospital. The sampling technique used Total Sampling, and the total sample was 52 respondents. The data analysis technique used the Spearman Rank test. The results of this study obtained the age (p 0.001, rho 0.500); gender (p 0.28, rho 0.150); GCS (p 0.001 rho -0.662); RBG (p 0.001 rho 0.5) factors. Age factor, gender factor, GCS factor, RBG factor affect the length of stay of CKB patients.